Pengaruh Komunikasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Badan Penghubung Provinsi Jawa Tengah Di Kebayoran Baru Jakarta Selatan - Kholqiyah, Latifatun; Suprianto Suprianto (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the effect of communication and work discipline on employee performance at the Central Java Provincial Liaison Agency located in Kebayoran Baru, South Jakarta. The research employs a quantitative method with an associative approach to analyze the relationship and influence between independent and dependent variables. The study population consists of 50 employees who were all used as the sample through a saturated sampling technique. Data were collected through questionnaires and documentation, while data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. Hypothesis testing was carried out using the t-test to determine partial effects, the F-test to determine simultaneous effects, and the coefficient of determination (R²) to measure the contribution of the independent variables to the dependent variable. The results of the study indicate that communication has a significant effect on employee performance, and work discipline also has a significant effect on employee performance. Simultaneously, communication and work discipline have a significant influence on employee performance. The Adjusted R Square value of 0.518 shows that 51.8% of the variation in employee performance can be explained by communication and work discipline, while the remaining 48.2% is influenced by other factors outside this study. Therefore, it can be concluded that effective communication and a high level of work discipline play an important role in improving employee performance at the Central Java Provincial Liaison Agency in Kebayoran Baru, South Jakarta Keywords: Communication, Work Discipline, Employee Performance